Status Gizi Anak Balita Pasca Bencana Di Pengungsian Kelurahan Buluri Kota Palu Provinsi Sulawesi Tengah - Nasrul Nasrul; Putu Candriasih; Arifin N.A (Jurnal GIZIDO, 2019)
ABSTARCT Nutrition problem in infants arise due to disasters due to paralysis of health services, lack of clean water supply, environmental sanitation, post-disaster infectious diseases. This research is descriptive which aims to describe the nutritional status of children under five after a disaster in the Evacuation Village of Buluri, Palu City. The population in this study amounted to 53 toddlers while the large sample taken amounted to 22 toddlers. The results showed that the nutritional status of children under five years after the disaster based on the weight for age index were namely poor nutrition of 3 people (5.7%), malnutrition 13 (25.5%), good nutrition 17 (32.1%). Based on the height for age index were very stunted children amounted to 2 (3.8%), stunted 20 (37.7%), and normal 31 (58.5%). Based on the weight for height index the nutritional status of very thin children 3 (5.7%), thin 8 (15.1%) and normal 42 (72.2%). The conclusion that the nutritional status of children under five years after the disaster when viewed based on BB / U is increasing in number compared to before the earthquake. Whereas based on the indicators of TB / U or PB / U and BB / TB the increase is unknown because there is no data on the nutritional status of children that support before the earthquake. It is recommended to monitor the nutritional status of children under five before the disaster and after the disaster so that they can be seen.